Comparative Meta-analysis Effects of Nonnative Ants (Hymenoptera: Formicidae), Ground Beetles (Coleoptera: Carabidae), and Bark and Ambrosia Beetles (Coleoptera: Curculionidae) on Native Confamilials. Issue 3 (2nd April 2021) - Hartshorn, Jessica A; Coyle, David R
Abstract: Nonnative species often transform local communities to the detriment of native species. Much of the existing invasion ecology research focuses on the effects of a few extremely impactful species, and it is less clear how nonnative species which are not causing economic or ecological impacts alter closely related natives at risk of being displaced. Filling these knowledge gaps is critical because consequences of nonnative species are likely to vary depending on taxonomic scale, functional trait, and spatial or temporal niche. We conducted a meta-analysis to evaluate how biodiversity of native Formicidae (ants), Carabidae (ground beetles), and Scolytinae (bark and ambrosia beetles) species changes across a gradient of pressure from nonnative confamilials. We calculated Hill numbers for each group from data presented in literature and correlated native diversity metrics to proportion of nonnative species. Species richness of native ants was significantly negatively correlated with proportions of nonnative ants, whereas bark and ambrosia beetle metrics showed a nonsignificant negative correlation. Nonnative ground beetles had neutral effects on diversity of native ground beetles. Resulting contrasting patterns of invasive species effects on natives suggest complex biotic and abiotic factors driving effects of nonnative species in these groups. Our results suggest that a few extreme examples (e.g., red imported fire ants) drive most of the changes seen in native arthropod communities. To accurately assess impacts of invaders on native arthropod diversity, baseline data are needed, and community analyses must consider diverse functional traits of native taxa and improve the depth and breadth of community sampling.